Pengembangan E-LKPD berbasis PBL untuk meningkatkan berpikir kritis siswa sekolah dasar pada Pendidikan Pancasila - Rijal Sianturi; Daulat Saragi; Surya Dharma; Samsidar Tanjung; Yakobus Ndona; R Mursid (Universitas Pendidikan Indonesia, 2026)
The Problem-Based Learning (PBL) approach to Pancasila education in elementary schools positively impacts student engagement. However, the limited availability of interactive worksheets that facilitate and stimulate critical thinking remains a major obstacle in the field, so the development of innovative, cutting-edge teaching materials is urgently needed. This study aims to develop and test the feasibility, practicality, and effectiveness of a PBL-based E-LKPD on Indonesian diversity for fourth-grade students at SDN 066047 Medan Helvetia. Using the Research and Development (RnD) method with the ADDIE model, data were collected through observation, interviews, questionnaires, and tests. The results showed a high level of validity. This product proved to be very practical based on teacher and student responses. In addition, this E-LKPD significantly improved critical thinking skills. This PBL-based E-LKPD is very feasible, practical, and effective for application in learning. In its implementation, supporting infrastructure is still needed to facilitate the integration of E-LKPD as an interactive worksheet, so that students can also learn independently in the future.